Health risk perception and exercise intention of college students: a moderated mediation model of health anxiety and lay theories of health - Wang, Kun; Liu, Chen; Yang, Xiao; Wang, Yue (Frontiers in Psychology, 2024)
Background: Health risk perception is an important predictor of health-protective behaviors according the health belief model. However, the underlying mechanism connecting health risk perception and exercise behaviors is not well understood. The current study investigates how health risk perception predicts college students' exercise intention during post-pandemic era in China and the mediating effect of health anxiety and the moderating effect of lay theories of health.This cross-sectional study with convenience sampling was conducted on 767 students recruited from a province in central China. Health Risk Perception Scale, Health Anxiety Scale, and Lay theories of Health Scale and The Chinese version of the Exercise Intention Scale were used to measure the level of health risk perception, health anxiety, and implicit health theory and exercise intention.The results of the moderated mediation model indicated that health risk perception of college students significantly and positively predicted exercise intention (β = 0.110,t＝2.852，p < 0.01). Meanwhile, the indirect effect of health anxiety on the relationship between health risk perception and exercise intention was significant.Furthermore, Lay theories of health buffered the association between health anxiety and exercise intention, according to moderated mediation analysis (β＝0.068，t＝2.067，P＜0.05). For college students with incremental theory, the influence of health anxiety on exercise intention was positively and statistically significant.College students' health risk perception would lead to health anxiety, which can positively impact their exercise intention. Besides, Lay theories of health could moderate the effect of health anxiety on exercise intention. The results also have practical implications for developing effective, applicable, and scalable interventions to promote physical exercise through reducing the entity theory of health or increasing the incremental theory .health risk perception, exercise intention, health anxiety, Lay theories of healthDuring the COVID-19 pandemic, as there are no effective antiviral drugs to control the pandemic, and it would take much longer than expected to achieve herd immunity through vaccination, people mostly adopt health preventive behaviors such as wearing masks and social distancing (1). In the post-pandemic era, there is a growing awareness that improving physical fitness and disease resistance may be of the utmost importance. It is known to all that physical